Sams Teach Yourself Adobe® Dreamweaver® CS5 in 24 Hours - Bruce, Betsy; Ray, John 1971-; Ness, Robyn (Sams teach yourself, 2011)
In just 24 lessons of one hour or less, this book will show Dreamweaver beginners and upgraders how to create world-class web pages and sites with Adobe Dreamweaver. In this book's straightforward, step-by-step approach, each lesson builds on the previous ones -- helping you master all the essentials of Adobe's newest version of Dreamweaver from the ground up. Friendly, accessible, and conversational, this book gives Dreamweaver beginners a practical grounding in the entire package, without ever becoming overwhelming or intimidating. A new interactive Online Learning Lab will help you supplement the lessons in the book with step-by-step video walkthroughs of all the book's examples, detailed answers to the end-of-chapter quizzes, and all the files needed to complete the book's hands-on exercises.